(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To assess pain intensity using the NIPS and identify related factors during procedures in newborns at the Neonatal Intensive Care Unit, Pediatrics Center, Bach Mai Hospital. Methods: A cross-sectional descriptive study was conducted on 100 newborns undergoing invasive procedures without prior analgesia/sedation (4-6 hours) from October 2024 to October 2025. Pain was assessed using the NIPS score. Results: Preterm infants accounted for 76%, and males accounted for 68% of the study population. Arterial blood sampling was the most common procedure (65%), followed by peripheral venous catheter insertion (22%). 73% of infants experienced acute/severe pain (NIPS > 4). Arterial blood sampling caused the most severe pain (83.1%); Peripheral intravenous cannulation (80,6%); whereas 100% of intramuscular injections caused only mild to moderate pain. Physiologically, the heart rate increased by an average of 19 bpm, and SpO2 decreased by 3.7% during procedures; these changes were statistically significant (p < 0.0001). No statistically significant correlation was found between pain intensity and gender, gestational age, or birth weight (p > 0.05) Conclusion: These findings underscore the urgent need for implementing interventional pain management strategies (pharmacological or non-pharmacological) for routine invasive procedures in the Neonatal Intensive Care Unit.